Hijab Fantasy on Instagram: Community Fantasy Theme for Vanilla Hijab Brand - Ramadhani, Amelia; Utari, Prahastiwi; Hastjarjo, Sri (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
In the contemporary era, the hijab is no longer exclusively associated with a specific demographic. Its meaning has evolved and is now widely accepted within the community. While the hijab is a mandatory practice for Muslim women, it has also become a fashion statement. The growing acceptance of hijab has led to the emergence of local hijab brands. This article examines the use of social media, particularly Instagram, to examine communication between groups of hijab users, focusing on customers of a particular brand of hijab, namely Vanilla Hijab. Observing this group behavior used fantasy, emphasizing how individuals achieve a shared reality through communication. Individuals in the group conducted shared reality-seeing behavior among individuals guided by stories that reflect how reality is confirmed. The reinforcement of shared reality is repeated through personal, group, or community achievements and takes the form of stories or tales. In examining the theme of hijab customer group fantasy, the researcher employed a qualitative case study research method by conducting interviews with female Vanila Hijab customers. Producers use Instagram social media not only to inform the public about Vanilla Hijab's activities and introduce its products but also to build community involvement and receive input from a segmented audience. The findings indicate that group members added numerous fantasy themes to maintain group communication and foster group culture.